The History of Topolovac Estate: An Analytical Perspective on Spatial Dynamics and Socioeconomic Transitions (Povijesni prilozi (Historical Contributions), 2025)
This research paper explores the historical trajectory of the Topolovac estate, located southeast of Sisak, from its earliest mentions in medieval sources to its modern-day status. It presents a comprehensive synthesis of scattered historical data, offering new insights into noble land ownership, economic structures, and spatial transformations. The estate’s origins are linked to the Hungarian noble family Töttös de Bátmonostor et Blinja, whose control over the land in the 14th and 15th centuries marked the beginning of its documented history. Subsequently, land ownership transitions, from the Branković despots and Berislavić family to the Keglević counts, shaped the estate’s legal and administrative frameworks, influencing its function within the feudal system. The military significance of Topolovac, particularly during Ottoman incursions in the 16th century, is examined through historical records referencing fortifications and strategic positioning. In the early modern period, the estate became a key agricultural and economic centre, integrating new infrastructural developments while maintaining traditional feudal structures. The study also addresses the estate’s transformation in the 19th and 20th centuries, highlighting its transition from noble property to state administration and, later, privatization. Furthermore, this research consults cartographic and archival documentation, drawing from historical maps and land surveys to reconstruct the estate’s spatial development. By integrating archival research, historical topography, and conservation perspectives, this paper aims to contribute to the understanding and contextualization of Topolovac, its physical landscape and built heritage within the ongoing preservation and conservation initiatives.